Legal Actions Of Notaries Who Feel Aggrieved By The Decision Of The PTUN Court On Dismissal In PTUN Decision Number 200/PK/2022 In Jakarta - Susanti, Santi; Sentot Sudarwanto, Albertus; Tuhana, Tuhana (International Journal of Educational Research & Social Sciences, 2024)
As a public official, a Notary can be dishonorably dismissed if proven to have committed a criminal offense, as stipulated in the Notary Position Law. Although regulations related to dishonorable dismissal for notaries already exist, they are considered somewhat unclear. The issues discussed in this study include the substance of legal remedies for notaries who are dishonorably dismissed due to criminal convictions with a threat of less than five years. The research method used is normative juridical, with data collection through document study and literature review. The analytical approach used is qualitative. The research findings regarding the substance show that criminal offenses that can lead to dishonorable dismissal for notaries are criminal offenses with a prison sentence of 5 (five) years or more that have obtained legal force, whether committed in a personal or official capacity. Furthermore, the legal remedy for a Notary who is faced with dishonorable dismissal when convicted with a sentence of less than five years is to file a lawsuit to the State Administrative Court. This lawsuit is addressed to the Minister of Law and Human Rights as Defendant I, and the Notary as Defendant II.